Upaya Pengurus Cabang Nahdlatul Ulama Dalam Menciptakan Kemandirian Ekonomi - M. Zikwan; R. Fakhrurrazi; Muhammad Ihwan (Program Pascasarjana Universitas Ibrahimy, 2024)
PCNU Situbondo plays a strategic role in fostering economic independence amidst the challenges of economic globalization. Globalization has significantly impacted the local economy, including increasing dependence on foreign products and intensifying competition. To address these challenges, PCNU Situbondo acts as an agent of change through various programs focused on community-based local economic empowerment. This study aims to analyze the efforts of PCNU Situbondo in fostering economic independence. The research employs a descriptive qualitative method, with data collected through interviews, observations, and documentation. Data analysis in this study involves reduction, display, and conclusion. Data validity is ensured through triangulation. The findings indicate that PCNU Situbondo functions not only as a religious organization but also as a driving force in community economic development. Its roles as Development Agent, Prime Mover of Development, and Public Sector Partner highlight its impact. Initiatives such as Situbondo Konveksi Nahdliyyin and Koperasi 234 demonstrate success in promoting local economic growth.